4D Printing of Humidity‐Driven Seed Inspired Soft Robots (Adv. Sci. 9/2023). Issue 9 (24th March 2023) - Cecchini, Luca; Mariani, Stefano; Ronzan, Marilena; Mondini, Alessio; Pugno, Nicola M.; Mazzolai, Barbara
Abstract : Soft Robotics In article number 2205146, Stefano Mariani, Nicola M. Pugno, Barbara Mazzolai, and co‐workers develop a seed‐inspired soft robot using 4D printed biodegradable polymers. Driven by humidity changes, the artificial seed adapts its morphology to interact with soil roughness and cracks, exploring a sample soil. In perspective, the soft robot shows great potential as a battery‐free wireless tool for environmental monitoring.